Superconductor digital RF development for software radio. - Brock, D.K (IEEE Communications magazine)
We review a new ?direct digitization? approach for ?digital RF? architectures for software radio. Although direct digitization usually implies the simultaneous digitization of all channels in a particular band at a downconverted IF, we use this term to refer exclusively to the direct digitization of all bands, from near DC to RF. Furthermore, we present results on band selection and digitization of RF signals directly at the carrier frequency with high resolution. These novel approaches are enabled by a superconductor analog-to-digital converter technology using an ultra-fast IC logic known as Rapid Single Flux Quantum (RSFQ) logic, with performance capable of enabling envisioned software radios